Is there a religious dimension to concern about farmer-herder conflicts in Nigeria? - Tuki, Daniel (International studies quarterly, 2025)
Despite the high incidence of farmer–herder conflicts in Nigeria, large-N quantitative research on the religious dimension of these conflicts remains scarce. This study addresses that gap using data from Rounds 7 and 8 of the Afrobarometer surveys conducted in Nigeria in 2017 and 2020, respectively. Specifically, it examines how religious affiliation and the religious composition of an area influence concerns about farmer–herder conflicts. Regression analysis reveals no significant difference in concern between individuals living in predominantly Muslim versus Christian areas. However, religious affiliation plays a crucial role, with Muslims generally expressing less concern about these conflicts than their Christian counterparts. Disaggregating the data by survey year, a shifting pattern emerges: In 2017, individuals in predominantly Muslim areas were less concerned about farmer–herder conflicts than those in Christian areas, but by 2020, this trend had reversed. This shift may be linked to the rise in banditry involving nomadic pastoralists in Nigeria’s predominantly Muslim Northwest region. Notably, in 2020, Muslims and Christians exhibited no significant differences in their level of concern. Further analysis shows that Muslims and residents of predominantly Muslim areas are more likely to perceive a decline in farmer–herder conflicts and report fewer experiences of pastoral conflicts around their dwellings.